USE OF MACROMOLECULES ON THE RATE OF IN VITRO MATURATION AND EMBRYONIC DEVELOPMENT OF BOVINE OOCYTES - Santa Cruz P., Carolina (2014)
The effect of four supplements with macromolecules on the rate of nuclear maturation, oocyte division at 48 h and embryo development at 7 days post-fertilization was evaluated. Ovaries were collected in the slaughterhouse; oocytes with two or more layers of cells were selected and matured on TCM-99 enriched with macromolecule supplements: Polyvinylpyrrolidone (PVP), polyvinylalcohol (PVA), Bovine serum albumin (BSA), Foetal bovine serum (SFB). Oocytes were cultivated at 39 °C with 5% of CO2. Nuclear maturation was evaluated at 24 hours, classifying them as germinal vesicle, metaphase I, anaphasetelophase, metaphase II and degenerated. For the evaluation of the oocyte division and embryo development, oocytes were matured under the same conditions and fertilized with spermatozoa during 18 hours in KSOM-AA culture media, and then transferred to SOF culture media for 48 h. Significant differences on nuclear maturation (Metaphase II) were only observed between PVA and SFB (p<0.05). Furthermore, none significant differences on rate of division and embryonic development between treatments were observed. These results indicate that the macromolecule supplements provide similar conditions and requirements for the progression from metaphase I to metaphase II.